2018
DOI: 10.5037/jomr.2018.9102
|View full text |Cite
|
Sign up to set email alerts
|

Dental Stem Cells Harvested from Third Molars Combined with Bioactive Glass Can Induce Signs of Bone Formation In Vitro

Abstract: ObjectivesThe aim of this study was to assess the interaction of a bioactive glass scaffold with cells derived from dental pulp, dental follicle and periodontal ligament.Material and MethodsImpacted third molars were surgically removed from three young donors. Cells from the dental pulp, follicle and periodontal ligament tissues were isolated and expanded. Different cell populations were characterised using specific CD markers. Expanded pulp, follicle and periodontal cells were then seeded onto bioactive glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…46 hDPSC have relevant advantages including its high availability for autologous transplantation, which minimizes immunological rejection and ethical concerns. 47 hDPSC are multipotent cell populations largely present in the pulp chamber. hDPSC display mesenchymal-like characteristics, including self-renewal immunomodulatory properties, multi-lineage differentiation potential, and migration to the site of injury.…”
Section: The Emerging Role Of Dental Pulp-derived Stem Cellsmentioning
confidence: 99%
“…46 hDPSC have relevant advantages including its high availability for autologous transplantation, which minimizes immunological rejection and ethical concerns. 47 hDPSC are multipotent cell populations largely present in the pulp chamber. hDPSC display mesenchymal-like characteristics, including self-renewal immunomodulatory properties, multi-lineage differentiation potential, and migration to the site of injury.…”
Section: The Emerging Role Of Dental Pulp-derived Stem Cellsmentioning
confidence: 99%
“…Stem cells have been successfully isolated from human teeth and were studied to test their ability to regenerate dental structures and periodontal tissues. MSCs were reported to be successfully isolated from dental tissues like dental pulp of permanent and deciduous teeth, periodontal ligament, apical papilla and dental follicle (42)(43)(44). These cells were described as an excellent cell source owing to their ease of accessibility, their ability to differentiate into osteoblasts and odontoblasts and lack of ethical controversies (45).…”
Section: Stem Cells In Dentistrymentioning
confidence: 99%
“…Dental pulp stem cells are also of interest due to their ease of access, low donor site morbidity, and ability to differentiate into fibroblasts, nerve cells, endothelial cells, and odontoblasts in order to facilitate creation of new connective tissue [89] . Raspini et al [90] showed that dental pulp stem cells combined with bioactive glass scaffold that was treated with osteogenic medium in vitro showed good biocompatibility and osteogenic induction, making it a promising combination for hard tissue regeneration in the cranio-maxillofacial skeleton. However, the comparative efficacy of these cells between laboratory study and patient intervention remains to be seen [91] .…”
Section: Stem Cells and Growth Factorsmentioning
confidence: 99%